Prevalence of Osteopenia and Osteoporosis in the Kyrgyz Republic - Mamatov Sagynali Murzaevich1 , Farida Imanalieva2 , Chyngyzbek Mamazhakyp Uulu3 , Tugolbai Tagaev2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: To study the prevalence of osteopenia and osteoporosis (OP) among residents of the Kyrgyz Republic in 3 different age categories (18-39 years, 40-59 years, and 60-79 years), Give a comparative assessment of the prevalence of osteopenia and OP depending on gender and Based on the results, make proposals for the identification and diagnosis of osteopenia and OP in the Kyrgyz Republic. Materials and Methods: An Ultrasound bone densitometry (USBD) studied the Bone mineral density (BMD) in a total of 1200 people with 691 women and 509 men of 3 different age categories (18-39 years, 40-59 years, 60-79 years). Results: In the first group from 18-39 years, normal values found in 55.6% of people, osteopenia in 38.9% of people and OP in 5.5% of people. In the second group, from 40-59 years old, normal values found in 30.9% people, osteopenia in 60.2% people and OP in 8.9% people. Moreover, in the third group, from 60- 79 years, normal values were found in 9.5%, osteopenia is seen in 50.2% and OP in 40.3% of older people. Conclusion: Osteopenia and OP are quite common not only in the older age but even affect people of a younger age. The frequency of detection of osteopenia and OP is the highest recorded in older age groups. Women mostly exposed to OP that has pronounced degrees of BMD affection.